2020
DOI: 10.31393/bba38-2020-06
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of linear sizes of molars with cephalometric indicators of practically healthy men of the southern region of Ukraine

Abstract: The high prevalence of pathologies of the dental and tooth-jaw system both in Ukraine and abroad requires scientists to search for new, fundamental discoveries, in particular, to identify patterns of the relationship between cephalometric and odontometric indicators within certain ethnic populations. The purpose of the study is to establish the features of the correlations of computed tomography sizes of molars with cephalometric parameters of practically healthy men in the southern region of Ukraine. 33 pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…With the indicators of the facial skull, the largest number of reliable and medium correlations with the height of teeth, crowns, root length, parietal-lingual and mesio-distal dimensions of molars [12]. A similar study, however, conducted with the population of southern Ukraine, found correlations between most sizes of molars on the lower jaw and the length and height of the nose [24].…”
Section: Introductionmentioning
confidence: 90%
“…With the indicators of the facial skull, the largest number of reliable and medium correlations with the height of teeth, crowns, root length, parietal-lingual and mesio-distal dimensions of molars [12]. A similar study, however, conducted with the population of southern Ukraine, found correlations between most sizes of molars on the lower jaw and the length and height of the nose [24].…”
Section: Introductionmentioning
confidence: 90%
“…For residents of Western Ukraine, the largest number of significant correlations between molar size and cranial parameters were found with vestibular-lingual and mesiodistal tooth sizes, and for the facial skull with the height and length of the tooth root [12]. While for the inhabitants of Southern Ukraine the corresponding correlations were found with cranial indicators for tooth height and length of their roots, and for facial skull -with tooth height, root length, vestibular-lingual and mesio-distal dimensions [23].…”
Section: Introductionmentioning
confidence: 92%
“…Peculiarities of correlations of molar sizes with cephalometric indicators for both residents of the Western [13] and Southern regions of Ukraine [28] have been established. Features of regional indicators for children from different regions of the cube for cephalometric analysis by Rickett's established H. F. C. Suárez et al [29,30].…”
Section: Introductionmentioning
confidence: 99%